Immersive Herbal Medicine Museum as Sukoharjo's Cultural Identity - Rani Nur Aini; Farida Murti (Kirana Publisher (KNPub), 2026)
The Immersive Herbal Medicine Museum as Sukoharjo Cultural Identity is a concept for designing special museum facilities in Sukoharjo Regency, Central Java, which is designed to accommodate the functions of education, cultural preservation, and recreation based on immersive and multisensory experiences. Sukoharjo Regency is known as the center of the herbal medicine industry in Indonesia, but it does not yet have integrated facilities that represent this identity architecturally. The design method uses a descriptive qualitative approach through the analysis of three main characters: object characters (documentary, educational, interactive, multisensory), character actors (tourists, students, herbal medicine communities), and location characters (strategic, local identity, herbal culture). The synthesis of the three characters results in the basic concept of Immersive Journey of Jamu, which presents a comprehensive journey experience of knowing herbal medicine starting from history, raw materials, processing processes, benefits, to modern innovations. The application of digital technology such as projection mapping, motion sensors, interactive touchscreens, and audiovisual installations is an interactive medium for conveying information. The result is a space program that integrates immersive showrooms, herbal gardens, taste laboratories, herbal medicine workshops, and other supporting facilities in one coherent and representative unit of Sukoharjo's identity as a Jamu City.